1992
DOI: 10.1007/bf00229489
|View full text |Cite
|
Sign up to set email alerts
|

Grain isozyme and ribosomal DNA variability in Hordeum spontaneum populations from Israel

Abstract: Grain isozyme and ribosomal DNA (rDNA) variability was examined in Hordeum spontaneum populations sampled from 27 geographical sites in Israel. Considerable phenotypic variability was observed with variants of ADH1, EST3, EST10, BMY1 and WSP detected, which are not available in the H. vulgare gene pool. Seven new rDNA phenotypes were detected in the H. spontaneum populations. Shannon's index of diversity was used to partition the total phenotypic variation into between and within population components. Most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 19 publications
6
22
0
1
Order By: Relevance
“…Importantly, as a guide for collection and conservation of germplasm, a correlation betw^een drought tolerance and a marker on the long arm of chromosome 4 has been demonstrated in wild barley (Chalmers et al, 1992). Application of stable isotope measurements in breeding programmes has not been fully investigated, but Voltas et al (1996) have reported that the relationships between S^^C measurements and yield in barley varied with environment.…”
mentioning
confidence: 99%
“…Importantly, as a guide for collection and conservation of germplasm, a correlation betw^een drought tolerance and a marker on the long arm of chromosome 4 has been demonstrated in wild barley (Chalmers et al, 1992). Application of stable isotope measurements in breeding programmes has not been fully investigated, but Voltas et al (1996) have reported that the relationships between S^^C measurements and yield in barley varied with environment.…”
mentioning
confidence: 99%
“…Considerable allelic and haplotype diversity is found among wild barley populations (Nevo et al 1979(Nevo et al , 1986aSnow and Brody 1984;Jana et al 1987;Chalmers et al 1992;Dawson et al 1993;Badr et al 2000;Lin et al 2001Lin et al , 2002Morrell et al 2003Morrell et al , 2005. Evidence favoring a monophyletic, or possibly diphyletic, domestication of barley in the Jordan valley (Badr et al 2000;Salamini et al 2004) would predict a reduction of nucleotide diversity in alleles found among gene pools of domesticated versus wild Hordeum accessions in the wake of domestication bottlenecks.…”
Section: Introductionmentioning
confidence: 99%
“…6 and 7). Moreover, it is known from literature that some biological implications of the IGS size variation are related to general metabolism (Cluster et al 1987) and to ecological differentiation influencing the environmental adaptation (Flavell et al 1986a, Chalmers et al 1992). Samples 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 According to Reeder (1989), at least six control elements are present in the IGS of ribosomal genes.…”
Section: Discussionmentioning
confidence: 99%